Rhodium(I)-Catalyzed [2+2+1]-Carbonylative Cycloaddition of Diynes with Anthracene α-Diketone as the Source of CO - Jia, JingWen; Yamaguchi, Yoshiko; Ueda, Tatsuya; Yamada, Hiroko; Kakiuchi, Kiyomi; Morimoto, Tsumoru (Synlett, 2022)
We report on the use of anthracene α-diketone as a source of carbon monoxide (CO) in carbonylation reactions. Photoirradiation by a 5 W blue LED of a diyne in the presence of anthracene α-diketone and a rhodium(I) catalyst resulted in a [2+2+1]-carbonylative cycloaddition of the diyne to CO released from the anthracene α-diketone to give a high yield (up to 99%) of the corresponding cyclopentadienone. This is the first demonstration of a CO-gas-free carbonylation reaction using anthracene α-diketone. Light irradiation was a major factor both in the generation of CO from anthracene α-diketone and in the catalytic activity. A halogen lamp, a fluorescent lamp, or sunlight also served as a light source for this reaction. With this system, there is no need for an additional reagent for generating CO.
Keywords: anthracene α-diketone; [2+2+1]-carbonylative cycloaddition; diynes; cyclopentadienes; carbon monoxide